BUDAYA MINANGKABAU DALAM NOVEL HARTA PUSAKA CINTA KARYA DESNI INTAN SURI: KAJIAN POSTMODERNISME - Dwi Mutia Chan; Zuraida Khairani; Najmi Hayati (STKIP Pesisir Selatan, 2026)
This study aims to examine the representation of Minangkabau culture in the Novel Harta Pusaka Cinta by Desni Intan Suri by using the perspective of postmodernism. The focus of the study includes eclecticism, parody, pastiche, irony, and camp. This research uses a qualitative method with a descriptive approach. Data were collected using two main techniques, namely: (1) reading technique, namely by reading the novel repeatedly while looking at words, phrases, clauses, or sentences that reflect elements of Minangkabau culture; and (2) note-taking technique, namely recording the identified data for further analysis. The data analysis process is carried out through the stages of identification, classification, description, and interpretation. The results showed that the elements of postmodernism in Minangkabau culture reflected in the novel include: eclecticism, which is illustrated through the character's behavior towards the shift of Minangkabau culture due to the influence of outside culture; parody, which appears in the form of conveying Minangkabau culture with humorous nuances; pastiche, which appears in the character's actions that reflect a longing for past cultural values; irony, which is present through events that are contrary to expectations; and camp, which shows the blurring of identity. Through the perspective of postmodernism, the characters in the novel illustrate a response to the dynamics of the times.